SFRP4+ stromal cell subpopulation with IGF1 signaling in human endometrial regeneration - Bingbing Wu; Yu Li; Nanfang Nie; Xilin Shen; Wei Jiang; Yanshan Liu; Lin Gong; Chengrui An; Kun Zhao; Xudong Yao; Chunhui Yuan; Jinghui Hu; et al. (Cell Discovery, 2022)
Abstract Our understanding of full-thickness endometrial regeneration after injury is limited by an incomplete molecular characterization of the cell populations responsible for the organ functions. To help fill this knowledge gap, we characterized 10,551 cells of full-thickness normal human uterine from two menstrual phases (proliferative and secretory phase) using unbiased single cell RNA-sequencing. We dissected cell heterogeneity of main cell types (epithelial, stromal, endothelial, and immune cells) of the full thickness uterine tissues, cell population architectures of human uterus cells across the menstrual cycle. We identified an SFRP4+ stromal cell subpopulation that was highly enriched in the regenerative stage of the human endometria during the menstrual cycle, and the SFRP4+ stromal cells could significantly enhance the proliferation of human endometrial epithelial organoid in vitro, and promote the regeneration of endometrial epithelial glands and full-thickness endometrial injury through IGF1 signaling pathway in vivo. Our cell atlas of full-thickness uterine tissues revealed the cellular heterogeneities, cell population architectures, and their cell–cell communications during the monthly regeneration of the human endometria, which provide insight into the biology of human endometrial regeneration and the development of regenerative medicine treatments against endometrial damage and intrauterine adhesion.